2009
DOI: 10.1075/lic.9.2.04net
|View full text |Cite
|
Sign up to set email alerts
|

The effect of marked topic on memory in Hebrew and English

Abstract: This study examines and compares the effect of marked sentence structure on cognition and memory in English and Hebrew. It has been shown elsewhere that marked topic constructions in English have a significant effect on memory. Now, since Hebrew, like English, is an SV(O) (Subject-Verb-Object) language, the cognitive effect of marking the topic in Hebrew could be expected to be similar to the effect witnessed in English. However, the study presents data which attest unequivocally to the prevalence of marked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Thus, unlike in English, in Hebrew OF is not misconstrued as SVO, and therefore the recomputation process required in English OF is not required in Hebrew. And indeed, Netz and Kuzar (2010) have found that in Hebrew, in contrast to English, there is no difference in recall between the topics of LD and OF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, unlike in English, in Hebrew OF is not misconstrued as SVO, and therefore the recomputation process required in English OF is not required in Hebrew. And indeed, Netz and Kuzar (2010) have found that in Hebrew, in contrast to English, there is no difference in recall between the topics of LD and OF.…”
Section: Resultsmentioning
confidence: 99%
“…Like English, Hebrew is also an SVO language. However, as Netz and Kuzar (2010) point out, in Hebrew in the fronting of a definite direct object (e.g. et Tomer, Shoshi matz'a [Tomer, Shoshi found]), the fronted object is marked by the accusative case marker et.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation